2021
DOI: 10.20546/ijcmas.2021.1001.038
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Diversity of Sesame Genotypes Using Cluster Analysis and Principal Component Analysis

Abstract: Tanzania produces highest production of sesame (14.6%) of the world followed by Myanmar (12.78%) and India (12.4%). In India, the productivity is very low particularly in Rajasthan. The major reasons for low productivity are lack of fast-adapting cultivars, capsule shattering, uneven ripening, poor crop stand establishment, lower fertilizer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…The number of primary and secondary branches and increase in basal leaf area contributed to the increase in seeds per capsule in a positive direction. Similar results were reported by Singh et al (2018), Baraki et al (2020) and Deepak Gupta et al (2021).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The number of primary and secondary branches and increase in basal leaf area contributed to the increase in seeds per capsule in a positive direction. Similar results were reported by Singh et al (2018), Baraki et al (2020) and Deepak Gupta et al (2021).…”
Section: Resultssupporting
confidence: 91%
“…The number of primary and secondary branches and increase in basal leaf area contributed to the increase in seeds per capsule in a positive direction. Similar results were reported bySingh et al (2018),Baraki et al (2020) and DeepakGupta et al (2021). The important yield traits both through correlation and PCA analyses showed a negative association with days to maturity which was also observed byBaraki et al (2020).…”
supporting
confidence: 88%
“…Inter-correlation among the traits showed that days to 50% flowering showed significant and positive association with days to 80% physiological maturity, stem height from base to first branch, capsule length, oil content and protein content and negative association with internodal length, 1000-seeds weight and stover yield per plant at genotypic level while at phenotypic level it showed significant association with days to 80% physiological maturity, oil content and protein content. These results were in agreement with Gupta et al (2021) for days to 80% physiological maturity; Takele et al (2021) for days to maturity and oil content. Significant and positive association of days to 80% physiological maturity was observed with only two traits viz.…”
Section: Resultssupporting
confidence: 91%
“…Hence, direct selection for these traits may lead to development of high yielding genotypes of sesame. These results are in confrontation with Singh and Bisen (2018), Lalpantluangi and Shah (2018) for number of capsules per plant at genotypic level and for plant height, number of branches per plant at phenotypic level; Singh et al (2020) and Takele et al (2021) for number of capsules per plant, the number of branches per plant, plant height and harvest index; Patil and Lokesha (2018), Navaneetha et al (2019), Saravanan et al (2020) for number of capsules per plant, plant height and number of branches per plant; Abate et al (2018) for plant height, number of capsules per plant, stover yield/plant and harvest index; Haibru et al (2018), Singh et al (2018) and Disowja et al(2020) for number ofcapsules per plant, plant height; Gupta et al (2021) for harvest index; Singh et al (2018) for number of capsules per plant; Abhijatha et al (2017), Patil and Lokesha (2018), Jamir et al (2020) and Kumar et al (2022) for number of capsules per plant, number of branches per plant; Ravitej et al (2019) and Sasipriya et al (2022) for number of capsules per plant, number of branches per plant both at phenotypic and genotypic level; Abdou et al (2015) for harvest index, number of branches per plant, this relation indicates that the best yield was obtained with highly branched plants because capsules number increases with the degree of branching and thus ultimately increase seed production.…”
Section: S245mentioning
confidence: 99%
“…To know which trait or combination of traits would mitigate stress better, it is necessary to find a group of principal traits which can be obtained by principal component analysis (PCA) [ 91 ]. PCA showed that PC1 and PC2 are the important principal components as they contributed to the maximum variance in both optimal (63.62%) and stress conditions (75.62%), with an eigen value of more than one, which implies that the traits have a narrow angle in PC1 and PC2, and which may be used for indirect selection of the genotypes to mitigate the stress by creating better genetic recombinants [ 3 , 92 , 93 ]. However, most of the traits which are necessary for the survival of seedlings were showing positive correlation with H 2 O 2 and MDA in optimal condition, and had shown negative correlation in stress conditions.…”
Section: Discussionmentioning
confidence: 99%